Analysis of blood mature BDNF and proBDNF in mood disorders with specific ELISA assays. (January 2021) - Lin, Liying; Fu, Xi-yue; Zhou, Xin-Fu; Liu, Dennis; Bobrovskaya, Larisa; Zhou, Li
Abstract: Previous studies showed that blood BDNF levels in mood disorders were reduced. However, little is known about the changes of BDNF and its precursor proBDNF in lymphocytes. In addition, earlier studies using commercial ELISA kits cannot distinguish mature BDNF from proBDNF. We aimed to investigate the change of mBDNF and proBDNF levels in the peripheral blood and their diagnostic value in the mood disorders using a specific Enzyme-Linked Immunosorbent Assay (ELISA). Serum mBDNF levels were significantly decreased in major depressive disorder (MDD) (n = 90) and bipolar disorder (BD) (n = 15) groups ( P  < 0.0001), whereas there was no significant change in suicidal group (n = 14) compared to the control group (n = 96). In the subgroups of MDD, the serum mBDNF level in MDD patients with severe symptoms was significantly lower than that with moderate symptoms ( P  < 0.05). The serum mBDNF levels in antidepressant-free patients were significantly lower than in antidepressant-treated patients ( P  < 0.01). Serum mBDNF yielded good diagnostic effectiveness for MDD and BD with sensitivity and specificity around 80–83%. The levels of mBDNF, proBDNF and its receptor sortilin were upregulated in lymphocytes of MDD patients relative to control subjects. Specific ELISA assays for mature BDNF confirmed the reduction of serum mBDNF level in MDD and BD. The measurement of mBDNF level could be a potential diagnostic marker with a cut-off point at 12.4 ng/ml. Upregulations of proBDNF and mBDNF in lymphocytes of MDD patients might be considered as novel pathological biomarkers for MDD.